Penetrasi kekerasan: Analisis contoh kekerasan sebagai alat penetrasi budaya - Syahbani, Alfito Prarista Dwi; Ghozi, Ahmad; Nazilah, Nishfi Rohmatun; Fajrin, Nourleta Fatriyanti (Maliki Interdisciplinary Journal, 2024)
The use of violence as a means of cultural penetration is a phenomenon that is common with the times. This penetration involves the transfer of values and norms as well as violent practices from one culture to another. This article describes examples that show that violence is often used as a means to change or reinforce the existence of a foreign culture among local cultural authenticity. This phenomenon can lead to debates and even wars between individuals, groups and countries. The practice of penetration through coercion and violence will bring complex changes to existing cultures. This can be seen from the adaptation of local culture to the violent aspects of global culture that are rampant today. Many symbols of violence are adopted into aspects of today’s art or fashion, which may also change the local population’s perception of violence as something that is no longer dangerous. Therefore, it can be concluded that violent cultural penetration is not only a physical phenomenon, but also a social phenomenon with significant cultural implications. Stricter monitoring of the influx of foreign cultures is crucial to prevent violent representations. Such efforts are also needed to develop an understanding of how cultures exchange values and how the influence of violence can be controlled in the context of the culture.